1989
DOI: 10.1002/aja.1001860302
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the lingual apparatus of the domestic chicken, Gallus gallus, with special attention to the structure of the fasciae

Abstract: A detailed redescription of the mechanically interacting structural elements of the lingual apparatus of the domestic chicken, Gallus gallus, revealed the functional and constructional role of organized connective tissue (i.e., ligaments and fasciae) as structural elements that ensure the proper biomechanical interactions among the various structures within the lingual apparatus (e.g., cartilaginous and bony skeletal elements, muscles, salivary glands, epithelial structures). Fasciae, together with extrinsic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
75
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 24 publications
10
75
5
Order By: Relevance
“…It is allowed to roll from right to left and back. Also, our results showed that the mandible of the Rock dove is composed of two diverged rami, which are fused anteriorly through the mandibular symphsis this is similar to the results (Zweers, 1982 ;Homberger &Meyers, 1989 andIsmail, 2006a). Also, showed that the mandible provides sites for origin of these muscles: muscle branchiomandibularis in the medial surface while the lateral surface provides sites for origin of these muscles: muscle branchiomandibularis posterior., muscle stylohyoideus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is allowed to roll from right to left and back. Also, our results showed that the mandible of the Rock dove is composed of two diverged rami, which are fused anteriorly through the mandibular symphsis this is similar to the results (Zweers, 1982 ;Homberger &Meyers, 1989 andIsmail, 2006a). Also, showed that the mandible provides sites for origin of these muscles: muscle branchiomandibularis in the medial surface while the lateral surface provides sites for origin of these muscles: muscle branchiomandibularis posterior., muscle stylohyoideus.…”
Section: Discussionsupporting
confidence: 91%
“…The dorsal surface of the basihyale bony provides the sites of origin for the muscle hypoglossus posterior. Results of this study also showed that the ceratobranchiale is composed of bony element and show the same result in Chicken and Herrin gull (Homberger &Meyers, 1989 andAl-Jalaud, 1994a). The ceratobranchiale connects to the epibranchiale by a synchonodrosis between two bony elements as stated by (Zweers, 1982 ;Battacharyya, 1980Battacharyya, ,1990Al-Jalaud, 1994a, andAbdel-Rahmaan, 1998).…”
Section: Discussionsupporting
confidence: 77%
“…While many authors stated that the basihyal and urohyale of common moorhen are fused together and represent the supportive elements of the preglottal area, as well as the laryngeal mound . The apical end of the bony part of the urohyale is fused to the basihyale in the chicken (Homberger & Meyers, 1989). The present results showed that ceratobranchiale is composed of elongated rod-like bony element, similar in chicken and Herrin gull (Homberger & Meyers, 1989;Shawki & Al-Jalaud, 1994a).…”
Section: Discussionsupporting
confidence: 61%
“…The present results showed that the hyoid skeleton is a well developed in rock dove like the hyoid skeleton was found in the parrot (Homberger, 1986), in white throated kingfisher (Halcyon smyrnensis) and common buzzard (El-Beltagy, 2013) and in the Egyptian black kite (Shawki, 1995). The paraglossale forms the longest and elongated, unpaired arrow-shaped skeletal support of the free portion of the tongue in the rock dove it is very similar to the paraglossal of some species of common moorhen, Herring gull, chicken and the golden eagle (Homberger & Meyers, 1989;Shawki, & Al-Jalaud, 1994b;Parchami & Fatahian, 2010). The surface structures of the paraglossale usually indicate attachment sites for muscle or ligaments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation